Analysis of operational risk management in the Nigerian oil and gas industry - Dosunmu, Adebukola (2014)
This study explores the operational risks that are apparent in the Nigerian Oil and gas industry and the operational risk management (ORM) employed in mitigating such risks. In doing this, the study looked at the extent to which operational risk management has reached in the Nigerian oil and gas industry and how this operational risk management is carried out. Hence it involved researching if enterprise risk management (ERM) is used in managing such operational risk especially as ERM is considered by many authors to be the new risk management paradigm. The general consensus is that ERM and ORM are similar when it comes to managing operational risks. Existing literature on ORM is predominantly on financial institutions with little reference to its implementation in non-financial institution thus the study was done to shed some light on the existence of ORM in one of such 'non-financial industries' which is the Nigerian oil and gas industry essentially as the oil and gas industry face lots of operational risks ranging from need in health and safety, environmental pressures resulting from oil spill accidents to protecting industry image and minimizing of business interruptions as a result of the problems associated with Niger Delta region of the country in which most of the operations are carried out. The study found out that ORM does exist to a reasonable extent in managing risks in the Nigerian oil and gas industry and it is indeed closely linked with the process of enterprise risk management.